Pengaruh Budaya Organisasi Dan Pelatihan Kerja Terhadap Kinerja Pegawai Pada Suku Dinas Kependudukan Dan Pencatatan Sipil Kota Administrasi Jakarta Pusat - Rachel Darmajadi (Jurnal Manajemen, 2025)
Human resources are key in organisations, especially government organisations, it is influenced by organisational culture and job training on employee performance. This study aims to determine whether organisational culture and job training have a significant effect on employee performance partially or simultaneously. This study uses a quantitative method where the data collected is then processed using the SPSS version 25 application to analyse the results of the questionnaire and measure all existing variables with several tests, including validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, and hypothesis testing using multiple linear regression, determination test (R²), f test and t test. The results of the coefficient of determination (R²) use an R square value of 0.156, it can be concluded that organisational culture (X1) and job training (X2) simultaneously affect the employee performance variable (Y) by 15.6%. From the results of the f test and t test calculations, it can be seen that all organisational culture and job training variables simultaneously have a positive and significant effect on employee performance with a Sig value. 0.034 <0.05, and for the value of fcount is 3.688> ftabel is 3.23.